Out-of-hospital cardiac arrest (OHCA) Survey in Lombardy: data analysis through prospective short time period assessment - Villa, Guido Francesco; Kette, Fulvio; Balzarini, Federica; Riccò, Matteo; Manera, Matteo; Solaro, Nadia; Pagliosa, Andrea; Zoli, Alberto; Migliori, Maurizio; Sechi, Giuseppe Maria; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: The results of out-of-hospital cardiac arrests (OHCA) are usually reported through data collected collected via “ad hoc”  registries, but in large populations, samples of short time periods can be used to apply the results to the entire population. We would like to describe the situation of Lombardy to provide evidence on successful procedures, which may be carried out in a larger context. Methods: Observational, prospective, analytical, single cohort study in Lombardy population. Data of OHCA of cardiac aetiology, according to “Utstein Style”, with resuscitation attempts started by the Emergency Medical Service (EMS), were collected for 40 days subdivided in 10-day-periods in all seasons 2014-15 via Operating System “Emergency Management” (EmMa). Results: Of 1219 cases, 536 events of witnessed OHCA of presumed cardiac etiology were analyzed. Outcomes were: sustained Return Of Spontaneous Circulation ROSC (25.6%), Survival Event in Emergency Department (22.8%), Survival after 24 hours (21.2%) and Survival after hospital discharge at home 30 days after (11.2%). Statistically significant results were found in age, rhythm of presentation, and resuscitation by bystanders. Sex, seasonality and rescue timing did not differ statistically. Conclusions: Overall the thirty-day survival rate was similar to studies with larger databases. Our data are consistent with the concept that all emergency service should provide CPR instructions for every citizen who activate the EMS in the suspect of a SCA; further investigation should clarify how long interval could be useful for ROSC and sustained ROSC in patients resuscitated by lay people using CPR instructions.